Synthesis and characterization of a new vic-dioxime ligand and its complexes with cobalt(II), nickel(II) and copper(II) - Demirhan, N; Erden, I; Avciata, U (NATL INST SCIENCE COMMUNICATION-NISCAIR, 2004)
A new vic-dioxime ligand (LH4), 1,10-phenanthrolino-5,6-bis(2,3-dihyroxyimino-1-aza) propane has been synthesized from the reaction of 5,6-diamino-1,10-phenanthroline with anti-chloromethylglyoxime. The ligand reacts with Co(II), Ni(II) and Cu(II) salts to form complexes. The complexes have been characterized by FTIR, H-1 NMR (DMSO-d(6)), elemental analyses and magnetic measurements. Protonation constants of the ligand and overall formation constants of the complexes have been calculated from potentiometric data using the program TITFIT.
Keywords: CRYSTAL; Chemistry